The Urgency Of Counseling Services In Overcoming Erroring Behavior Of Students In Modern Islamic Boarding Schools - Nurussakinah Daulay; Salim Salim; Delianti Putri (At-Tarbiyat, 2022)
This study examines the analysis of the forms of deviant behavior of students in modern Islamic boarding schools, the efforts made in overcoming the deviant behavior of students in modern Islamic boarding schools, and to determine the factors supporting and inhibiting the implementation of guidance and counseling in overcoming abnormal behavior of students. The location of this research is in Daar Al-Uluum Islamic Boarding School Kisaran, Asahan. This research is qualitative research with a phenomenological approach. Data was collected using observation techniques, in-depth interviews, and documentation studies. Research informants consisted of boarding school administrators, male students, and female students. The results of this study indicate that: The general forms of deviant behavior carried out by students at the Islamic boarding school of Daar Al-Uluum Kisaran, Asahan is truancy, smoking, fighting. Counseling efforts and services in overcoming students' deviant behavior at Pondok Pesantren Daar Al-Uluum Kisaran, Asahan take preventive, repressive, and curative actions. The factors causing students' bad behavior at Pondok Pesantren Daar Al-Uluum Kisaran, Asahan are friends, family factors, and self-control.